2019
DOI: 10.1002/chem.201903604
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Flipper Probes: Comprehensive Twist Coverage

Abstract: To image the membrane tension in living cells, planarizable push–pull probes have been introduced. The first operational probe is built around two dithieno[3,2‐b:2′,3′‐d]thiophenes (DTTs) that are twisted out of co‐planarity and polarized with donors and acceptors at either end. In this report, the chemical space available for the twisting of “flipper probes” is assessed comprehensively. The result is, not surprisingly, that every atom matters: Removal of one methyl group in the twist region yields probes that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

9
0

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 84 publications
4
29
0
Order By: Relevance
“…It thus indicated that, as soon as photoreleased from the ER surface within a few minutes (Figures 2 B,C, S2), flipper 1 re‐distributes among all membrane leaflets accessible by free diffusion (Figures 2 D, S4). Only the most ordered membrane, here the PM, is labeled because planarization of flipper 1 in such membranes suppresses competing non‐radiative decay and thus increases emission intensity decisively, [5] as previously illustrated in FLIM images and computational simulations of phase‐separated membranes [12, 27, 28] (Figure 2 B,C).…”
Section: Figurementioning
confidence: 76%
“…It thus indicated that, as soon as photoreleased from the ER surface within a few minutes (Figures 2 B,C, S2), flipper 1 re‐distributes among all membrane leaflets accessible by free diffusion (Figures 2 D, S4). Only the most ordered membrane, here the PM, is labeled because planarization of flipper 1 in such membranes suppresses competing non‐radiative decay and thus increases emission intensity decisively, [5] as previously illustrated in FLIM images and computational simulations of phase‐separated membranes [12, 27, 28] (Figure 2 B,C).…”
Section: Figurementioning
confidence: 76%
“…The emission maximum around 600 nm is nearly mechano-insensitive because the emission always occurs from a fully planarized excited state. 6 This combination of planarization and polarization in equilibrium in the ground state often occurs in nature, from lobster pigmentation 15 17 to the chemistry of vision, 18 20 but is unexplored in the design of fluorescent probes. Most other fluorescent membrane probes operate in the excited state by different mechanisms, such as intramolecular charge transfer (ICT), twisted intramolecular charge transfer (TICT), excited-state intramolecular proton transfer (ESIPT), photoinduced electron transfer (PET), Förster resonance energy transfer (FRET), and the like.…”
Section: Introductionmentioning
confidence: 99%
“…1b ), and the appearance of some vibrational finestructure. 16 Flipper-TR is composed of (i) a triazole-carboxylate hydrophilic head for positioning into the membrane and stability, and (ii) a DTT-based chromophore responsible for the spectroscopic behavior. It has been hypothesized that the two DTT flippers may respond to lateral forces by switching between planar and nonplanar conformations as a result of twisting around the “mechanosensitive” dihedral Θ ( Fig.…”
Section: Introductionmentioning
confidence: 99%